The Impact of Internet of Things (IoT) on Integrated Sustainability Accounting Monitoring and Reporting - Cherilyn Harjanto; Clarissa; Nadjwa Fazira Jullyeta J (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study aims to analyze the role of IoT in improving the accuracy and efficiency of monitoring, identifying the impact of IoT on transparency and accountability of sustainability reporting, exploring the potential of IoT in supporting real-time data-based decision-making, and evaluating the challenges and opportunities of implementing IoT in integrated sustainability accounting. This study adopts a quantitative approach with a survey method to analyze the impact of the Internet of Things (IoT) on integrated sustainability accounting monitoring and reporting. The research uses multiple linear regression for data analysis to identify significant relationships between IoT and sustainability accounting practices. To ensure the accuracy and reliability of variable measurement, the validity and reliability of the measurement instrument were rigorously tested. The findings reveal that IoT significantly enhances accuracy, efficiency, transparency, and accountability in integrated sustainability accounting monitoring and reporting, as well as supports real-time, data-driven decision-making. All hypotheses (H1 to H6) were found to be significant, confirming the positive effects of IoT on various aspects of sustainability reporting and operational effectiveness. The study is limited to examining the application of IoT in integrated sustainability accounting monitoring and reporting, focusing on the role of sensor technology and connected devices. It excludes industrial-scale applications and broader aspects of IoT-ESG integration, constrained by the resources and time available for the research.